Pengaruh Komposisi Serat Wlingi (Mansaiang) Terhadap Sifat Kekuatan Tarik - Sutrisno, Sutrisno (LPPM Universitas Merdeka Madiun, 2021)
Abstractâ€” The purpose of this study was to determine the effect of the composition of the material using the wlingi fiber fraction with polyester resin on tensile strength. The materials used in this study were Wlingi fiber and BQTN polyester resin. Making was done by hand lay up process. After reaching the desired holding time, the mold is put into the oven and processed and the specimen is removed from the mold. After obtaining four specimens of wlingi fiber variations, the tensile strength testing process was carried out according to ASTM 638. The results of this test indicate that the composition of the material with a wlingi fiber weight fraction of 40% Tensile strength of 118.76 MPa, a strain of 1.32 mm / mm, and a modulus of elasticity of 12355 MPa.Â Keywordsâ€”: tensile strength; wlingi fiber; BQTN resin.